2017
DOI: 10.1016/j.jmau.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Skeptical approaches concerning the effect of exposure to electromagnetic fields on brain hormones and enzyme activities

Abstract: This review discusses the effects of various frequencies of electromagnetic fields (EMF) on brain hormones and enzyme activity. In this context, the mechanism underlying the effects of EMF exposure on tissues generally and cellular pathway specifically has been discussed. The cell membrane plays important roles in mediating enzymatic activities as to response and reacts with extracellular environment. Alterations in the calcium signaling pathways in the cell membrane are activated in response to the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 82 publications
1
11
0
Order By: Relevance
“…When using a mobile phone, a close distance between the phone and the breasts exists, and the breasts are exposed to significant amounts of radiofrequency radiation, which contributes to DNA damage and promotes the development of breast cancer ( 3 ). In addition, it has been reported that melatonin is a hydroxyl radical scavenger, and decreased expression of melatonin has been indicated to enhance the oxidative damage and increase breast cancer risk ( 52 ). Chang et al ( 53 ), conducted a randomized controlled trial to estimate the effect of iPad notebooks on melatonin expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using a mobile phone, a close distance between the phone and the breasts exists, and the breasts are exposed to significant amounts of radiofrequency radiation, which contributes to DNA damage and promotes the development of breast cancer ( 3 ). In addition, it has been reported that melatonin is a hydroxyl radical scavenger, and decreased expression of melatonin has been indicated to enhance the oxidative damage and increase breast cancer risk ( 52 ). Chang et al ( 53 ), conducted a randomized controlled trial to estimate the effect of iPad notebooks on melatonin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the radiofrequency emitted by mobile phones or electronic devices can induce both DNA damage and the suppression of melatonin expression. Suppression of the production of melatonin may cause an increased production of estrogen, resulting in a subsequent increase in the risk of breast cancer ( 25 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some occupational groups such as power plant workers are exposed to high levels of ELF‐EMFs caused by power transmission lines compared to the general public, which is a matter of concern 1,2 . Exposure to electromagnetic fields affect brain function, hormones, and enzymatic activity, and its effect depends on the frequency and duration of exposure 3,4 . Several potential reactive mechanisms such as oscillatory resonance, and the mediating mechanism of reactive oxygen species (ROS) that induce bipolar momentum may explain the mechanism of action of these fields, 5‐7 among which, the radical pair mechanism has been more widely accepted 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The most sensitive tissues and organs of mammals under such conditions are the nervous system and blood, as well as the heart and the liver (Khnychenko & Sapronov, 2003;Volkova & Meleshkina, 2008;Sawa et al, 2017). Computerization of workplaces, which has led to the inactive condition of employees during the working day and an increase in the time spent by both children and adults sitting at the computer is a stressful load that worsens health (Warille et al, 2017). The chronic stage of stress conditions leads to a decrease in blood circulation due to vasoconstriction and an increase in the risk of developing hypoxic conditions in many organs and the nervous system (Ushakova et al, 2010;Tkachenko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%